2005
DOI: 10.1598/jaal.48.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Re‐envisioning Reading and Writing Through Combined‐Text Picture Books

Abstract: Combined‐text picture books unite multiple genres, providing nuanced information on a single topic from the unique lens of each genre. By providing guided practice in reading and writing a combined‐text picture book, teachers can help students develop sensitivity to different types of texts, to what they do and how they do it. Such sensitivity can give students a foundation for selecting appropriate strategies for reading and writing effectively in a wider variety of genres. This article describes the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The drafting activity using the Venn-diagram assisted them to put the general classification and description in a right way. It prepares a visual summary of a discussion of a topic (Dean & Grierson, 2006). The visual summary of a discussion allowed the students to interact with text ideas, considered them from different points of view, and conversed internally about them (Kucan & Beck, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drafting activity using the Venn-diagram assisted them to put the general classification and description in a right way. It prepares a visual summary of a discussion of a topic (Dean & Grierson, 2006). The visual summary of a discussion allowed the students to interact with text ideas, considered them from different points of view, and conversed internally about them (Kucan & Beck, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It also contributes to keeping students actively involved and allows students to organize their ideas about the concepts (Junaid, 2012 Research has been conducted to investigate Venn-diagram strategy in the EFL classroom and particularly in writing class. Dean and Grierson (2006) investigated re-envisioning reading and writing through combined-text picture books. The result showed that the writing process using a graphic organizer in the form of Venn-diagram encouraged students to find a topic after which teachers can begin helping students through the inquiry and investigation preparing them to write.…”
mentioning
confidence: 99%
“…Picture books constitute a sequence of images with a narrative structure and brief text to convey stories and thus elicit the interest of readers and attract their attention, enabling them to focus on reading (Dockett, Perry, & Whitton, 2006). Therefore, some studies use picture books as teaching materials for examining the effect of picture books on subject learning and reading (Beveridge & McLeod, 2009;Dean & Grierson, 2005).…”
Section: Experimental Tool For Reading: Picture Booksmentioning
confidence: 99%
“…Previous studies (Dean & Grierson, 2005;Ma & Wei, 2015) have indicated that the two picture books, both of a moderate difficulty level, are separately suitable for the two parties (i.e., children and adults).…”
Section: Experimental Tool For Reading: Picture Booksmentioning
confidence: 99%
“…For example, suggesting that picture books containing strong visual imagery, such as Let's Get a Pup (Graham 2001) could be used to dispel misconceptions and stereotypes about families' appearances is a practice often associated with critical literacy (see for example Luke & Freebody, 1999;Martino, 1999). In this vein, numerous literacy researchers have argued for using picture books when discussing texts with younger children and adolescents to explore content, ideology, and non mainstream issues ( Albright, 2002;Dean & Grierson, 2005;O'Brien, 2001). …”
Section: Revue Des Sciences De L'éducation De Mcgill • Vol 47 N O 3 mentioning
confidence: 99%